Household Financial Literacy Among Oil Palm Farming Families: A Qualitative Descriptive Analysis - Ayu Ashari; Reza Reza; Kadori Haidar; Sutrisno Sutrisno (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study examines household financial literacy among women in oil palm farming families, a sector known for its economic volatility due to fluctuating commodity prices and limited access to financial information. Using a qualitative descriptive approach, data were collected through in-depth interviews and direct observations with women responsible for managing household finances in oil palm smallholder environments. The data were analyzed through stages of reduction, presentation, and conclusion drawing. The findings reveal that household financial literacy among these women is generally adequate, particularly in understanding income sources, essential expenditures, and the importance of prioritizing needs over wants. Respondents demonstrated the ability to manage income through budgeting decisions and to handle debt responsibly by ensuring timely repayment. However, financial challenges remain, especially due to the absence of systematic financial recordkeeping and limited long-term budgeting practices. These limitations often lead to difficulties in managing household finances during periods of price fluctuation or reduced harvest yields. The study emphasizes the need for strengthened financial education programs to support better planning, recording, and resilience in agricultural household economies.